Odontogenic keratocyst cyst: Odontogenic keratocyst cyst - Vivaldy, Reyhan; Mubarak, Husni (Makassar Dental Journal PDGI Makassar, 2025)
Odontogenic keratocyst cyst (OKC) is a rare odontogenic cyst that commonly affects the mandible. Carnoy solution in OKC is expected to repair the remaining cyst cells after removal thereby reducing the recurrence rate. Platelet rich fibrin (PRF) was applied to the cyst defect as it has been widely used as an autogenous graft material that can accelerate physiological wound healing and new bone formation. This case report describes the management of OKC before and after cyst enucleation in the mandible using carnoy solution and PRF. A 42-year-old male came to RSGMP Hasanuddin University with complaints of a lump on the left mandible since ±3 months ago. Intra oral examination, enlargement of the vestibulum region of teeth 33-34 measuring ±2x2x2 cm with palpation pain (-), crepitation (+). OPG x-ray and aspiration test were performed and a cloudy yellow liquid was obtained. The cyst was enucleated, applied carnoy solution and PRF, and histopathological examination was performed with OKC results. Four months postoperatively there were no complaints, good wound healing, and no enlargement. Control radiographs showed better bone formation than after surgery. It was concluded that enucleation of a cyst on the mandible to remove the cyst, prevent recurrence by applying carnoy solution and PRF to the cyst defect.